Genital Microbiota of Women From Six Ethnic Groups With and Without Human Papillomavirus Infection in Shangri-La, China - Liu, Chen-Jian; Xiao, Wen-Yu; Fang, Jun-Feng; Dong, Yong-Hong; Ye, Ke-Fan; He, Meng-Ping; Wang, Yan-Song; Li, Xiao; Zhao, Zhi-Min; Yuan, Tao; Zhao, Ting; He, Chun-Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background A diversity of microorganisms is associated with human health and exists in a state of dynamic equilibrium. This diversity has direct implications for the assessment of susceptibility to infectious diseases, especially human papillomavirus (HPV) infection. Methods Here, we investigated the relationships between HPV infection and vaginal, cervical, and gut microbiota composition and assessed the levels of genital immune mediators. We selected a multiethnic area in Yunnan Province, China, to collect samples from healthy women of childbearing age. A total of 82 healthy women of childbearing age were included in this study. Vaginal, cervical, and rectal swabs were collected to analyze the microbial community, and cytokines were analyzed in some samples. Findings Different proportions and types of HPV infection were detected in cervical (44%), vaginal (18%), and rectal (18%) swabs. HPV detected in cervical swabs was generally a high-risk type, while low-risk HPV types were primarily detected in vaginal and rectal swabs. There were some differences in this proportion as well as in the microbial community composition among different ethnic groups. Rectal samples exhibited the highest diversity index, while vaginal samples displayed the lowest diversity index. Lactobacillus dominated most of the vaginal samples, was decreased in HPV-positive samples, and differed among different ethnic groups. However, the sequence proportion of Lactobacillus in the cervix exhibited the opposite trend in those affected by HPV infection. The dynamic balance between the potential pathogens Gardnerella and Lactobacillus determines the health of the female genital system. Interpretation This study constitutes the first step toward personalized medicine for women’s reproductive health, wherein differences between the genital microbiomes of individuals would be considered in risk assessment and for subsequent disease diagnosis and treatment.